Quantification of porosity in extensively nanoporous thin films in contact with gases and liquids - Netanel Shpigel (Nature Portfolio, 2019)
Thin porous layers are largely used, but a reliable method to quantify their porosity is missing. Here the authors demonstrate a method, based on quartz crystal microbalance measurements with dissipation monitoring, for accurate assessment of porosity and mechanical properties in thin porous films.